THE ISSUES OF YOUTH IN THE TALK SHOWS IN THE IRAQI SATELLITE CHANNELS:: (An Analytical Study of the Shabab wa Banat Program at Al-Sumaria TV Channel and of the Hala Shabab at Al-Iraqia TV Channel) (A Research Drawn from a Master’s Thesis) - Hatem, Karar Mohamed; Ahmed, Hadi Abdullah (ALBAHITH ALALAMI, 2019)
The purpose of this research is to identify the youth issues in Talk Shows in the Iraqi satellite channels via monitoring a sample of episodes of the Talk Shows episodes which are concerned and analyzed the youth issues in the Iraqi satellite channels, namely, «Hala Shabab Program» at Al-Iraqia satellite Channel and «Shabab wa Banat Program» at Al-Sumaria satellite Channel by recording and re-watching them again. This research is classified as one of descriptive researches. The survey method was adopted in this study. For this purpose, the researcher prepared an analysis form. The researcher designed the content analysis form based on the research problem, goals and questions related to the research problem, which included the categories of analysis that were presented to the experts, relying on calculating the number of occurrences and percentages as a statistical measure. The researcher reached a number of results, the most important of which are: • The most prominent issues, that are displayed on «Hala Shabab» and «Shabab wa Banat» Programs, are focused on the artistry and cultural issues which are ranked firstly, and social issues are ranked secondly. • The programs of the research’s sample are focused on (male) gender, according to the nature of the guests’ gender, via a large percentage (87.5%) for the program of «Hala Shabab», and (76.47%) for the «Shabab wa Banat» These percentages are indicated that the two programs are focused on the dialogue with male guests more than the female guests whose percentages of hosting, in the research sample programs, are very poor. • The majority of programs’ guests, «Hala Shabab», «Shabab wa Banat», are respectively introduced the three high ranks (poet, civil activist and artist) for each. Such category of people reflects the concentration of this kind of program that hosts guests of these qualities in. • The programs of the research’s sample are also different in the methods of presentation of dialogue issues largely and variously, namely the program of «Hala Shabab» is based on the category of (one dialogue issue) which is presented a large percentage (90%). Whilst, the program of «Shabab wa Banat» is focused on the category (more than one dialogue issue) which is inevitably presented high percentage (95%). Thus, there are variations and differences in the methods of issues presentation in the programs of the research’s sample. The most prominent issues, that are displayed on Hala Shabab and Shabab wa Banat Programs, are focused on the artistry and cultural issues which are ranked firstly, and social issues are ranked secondly. The programs of the research’s sample are focused on (male) gender, according to the nature of the guests’ gender, via a large percentage (87.5%) for the program of Hala Shabab, and (76.47%) for the Shabab wa Banat program. These percentages are indicated that the two programs are focused on the dialogue with male guests more than the female guests whose percentages of hosting, in the research sample programs, are very poor. The majority of programs’ guests, Hala Shabab, Shabab wa Banat, are respectively introduced the three high ranks (poet, civil activist and artist) for each, which are reflected that these programs are concentrated, on these qualities, in hosting guests. The programs of the research’s sample are also different in the methods of presentation of dialogue issues largely and variously, namely the program of Hala Shabab is based on the category of (one dialogue issue) which is presented a large percentage (90%). Whilst, The program of Shabab wa Banat is focused on the category (more than one dialogue issue) which is inevitably presented high percentage (95%). Thus, there are variations and differences in the methods of issues presentation in the programs of the research’s sample.